A microporous core-sheath fiber-type flexible strain sensor
By adopting microporous core-sheath structure and composite conductive network layer in fiber-type flexible strain sensors, combined with the rubber layer design, the performance improvement problem of existing fiber-type flexible sensors under high tensile deformation is solved, and a wider range of results has been achieved The detection range and higher sensitivity and stability are suitable for wearable devices.
Patent Information
- Application Number
- CN202210478907.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-26
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2042-04-26
AI Technical Summary
The existing fiber-type flexible strain sensors have limited improvements in detection range, sensitivity and stability under the requirements of ultra-high tensile deformation, making it difficult to meet the wide application needs of wearable flexible devices.
The multi-porous AgNWs/CNTs/EGaIn/TPU strain sensor with microporous core-sheaven structure is used to prepare the core-sheaven structure by wet spinning and ultrasonic methods, and combined with the composite conductive network layer to improve the deformation ability and sensitivity of the sensor. Add a rubber layer to the outer layer to improve waterproofness and chemical environmental stability.
It realizes the continuous conductive path of the sensor under large strain, improves sensitivity and stability, expands the detection range, and enhances waterproofness and chemical environmental stability, and is suitable for the application of wearable flexible devices.
Smart Images

Figure CN114719737B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of sensor technology, and in particular to a fiber-type highly flexible stretchable strain sensor based on a microporous core-sheath structure. Background Art
[0002] In recent years, as people's pursuit of a healthy and comfortable lifestyle has grown rapidly, the demand for wearable sensors has increased, which has led to unprecedented attention for flexible electronic technology. Flexible strain sensors are a very important type of electronic device for information transmission and collection. Because of their good flexibility, ductility, and flexible and diverse structures, they can be used in real-world applications to achieve human-computer interaction, health testing, sports rehabilitation, etc., and are considered to be promising components in smart sensors. According to the working principle, existing flexible sensors are mainly divided into resistive, capacitive, piezoelectric, and triboelectric types. Among them, fiber-type flexible strain sensors based on the resistance principle are widely used and studied because of their simple structure, easy integration, and high working stability.
[0003] Since most traditional fiber-type strain sensors use materials with low elongation as fiber substrates, the strain range of the sensor is limited (within 200%), which greatly limits the applicable occasions of fiber-type strain sensors. The preparation of sensor fibers using wet spinning technology is an effective way to solve the above problems. However, the fibers obtained by simply wet spinning high molecular polymers with high elasticity, flexibility and stretchability (such as PVA, TPU and PDMS) have poor toughness, are easy to break and deform, and seriously affect the reuse of sensor devices. In addition, the outer conductive material enables the sensor to effectively improve the sensor performance of the sensor in principle. After stretching it, a significant resistance change can be obtained, thereby greatly improving the sensitivity and detection range. In the outer layer of the fiber-type flexible sensor, it is preferred to use highly conductive carbon (such as carbon nanotubes, carbon black, MXene), PEDOT:PSS or metal particles (such as silver nanowires, silver nanoparticles, gold nanoparticles) to form a conductive network.
[0004] So far, previous studies on the conductive layer of fiber-type flexible sensors have mostly focused on the use of a single conductive material, and rarely designed and used new composite conductive networks to improve device performance. The conductive network of existing fiber-type flexible sensors is relatively simple, resulting in limited improvements in the sensor's detection range, sensitivity, stability and other performance improvements under ultra-high tensile deformation requirements, making it difficult to meet the wide application needs of wearable flexible devices. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a microporous core-sheath fiber-type flexible strain sensor, and prepares a multi-microporous AgNWs / CNTs / EGaIn / TPU strain sensor with a core-sheath structure by wet spinning and ultrasonic methods. The microporous structure gives the sensor a wider deformation ability, detection range and lightweight characteristics, and matches the composite conductive network to ensure the continuous conductive path of the sensor under large strain, which is crucial for improving sensitivity. Therefore, it is very helpful to prepare a microporous structure on the substrate of the sensor in a reliable and feasible method, and to improve the elongation and toughness of the sensor substrate for the preparation of high-performance strain sensors. Starting from the material aspect, it is also of great significance to design and manufacture a composite conductive network sensor with higher performance than a fiber-type flexible sensor with a single conductive network.
[0006] The technical solution adopted by the present invention is as follows.
[0007] A microporous core-sheath fiber type flexible strain sensor comprises a microporous structural fiber as a core structure and a rubber layer as a sheath structure, wherein the rubber layer is coated on the periphery of the microporous structural fiber, the microporous structural fiber comprises a porous base fiber, and the surface of the porous base fiber comprises a composite conductive network layer, wherein the composite conductive network layer is a carbon nanotube conductive layer having conductive nanowires.
[0008] The porous base fibers of the microporous structural fibers have micropores of 0.1 to 5 μm and microcavities of 10 to 150 μm; the micropores and microcavities have inner surfaces with passivated oxide layers.
[0009] Among them, the matrix material of the porous base fiber of the microporous structure fiber is TPU, the inner surface of the passivated oxide layer is a metal oxide layer, preferably a Ga2O3 oxide layer; in the raw material of the porous base fiber, the liquid metal that can form the metal oxide layer is 1% to 10% of TPU, preferably 2.5% to 6.25%.
[0010] Wherein, the thickness of the composite conductive network layer is 50-1500nm, preferably 500±200nm.
[0011] Wherein, the conductive nanowires are one or more of silver nanowires, copper nanowires, gold-silver nanowires.
[0012] The rubber layer is made of a two-component liquid silicone rubber material, preferably Ecoflex rubber, more preferably Ecoflex00-10 to Ecoflex00-50 series.
[0013] The present invention also provides a method for preparing the microporous core-sheath fiber type flexible strain sensor, comprising the following steps:
[0014] S1: preparing a spinning solution containing sodium chloride, a matrix material and a liquid metal;
[0015] S2: Preparation of porous substrate fibers with stable microporous structure by wet spinning;
[0016] S3: sequentially depositing a CNTs conductive layer and a conductive nanowire on the surface of the porous base fiber to obtain a microporous structure fiber that can be used to further prepare a microporous core-sheath fiber-type flexible strain sensor;
[0017] S4: attaching the rubber layer raw material in an uncured state to the surface of the microporous structure fiber segment in a pre-stretched state;
[0018] S5: Curing the rubber layer raw material to obtain a sensor product.
[0019] Among them, in the step S1, the spinning solution components include sodium chloride, matrix material solution, and liquid metal diluent mixed in a weight ratio of 1:50:5-2:50:5, the matrix material solution is TPU and DMF mixed in a weight ratio of 1:3-1:5, and the liquid metal diluent is EGaIn and ethanol mixed in a weight ratio of 1:8-1:12.
[0020] Wherein, in the step S2, the specific process of wet spinning is to extrude the spinning solution into a coagulation bath through a syringe, and after stabilizing in the coagulation bath, dry the solution to obtain porous base fibers; the coagulation bath is a mixture of ethylene glycol and deionized water with a specific gravity of 1:1-1:1.2. In the step S2, the time for the spinning solution to stay in the coagulation bath after extrusion is more than 20 minutes, preferably 20-120 minutes, and more preferably 30-40 minutes.
[0021] Wherein, in the step S2, after the spinning solution is extruded and stabilized in the coagulation bath, the drying condition is to dry at 50-70°C for more than 2 hours.
[0022] Wherein, in step S3, the specific operation of depositing the CNTs conductive layer is: subjecting the porous base fiber to ultrasonic treatment at a temperature of 0-5° C. and a power of 350-400 W for 15-25 min.
[0023] Among them, in step S3, between depositing the CNTs conductive layer and the conductive nanowires respectively, the following steps are also included: drying the porous base fiber after depositing the CNTs conductive layer in an oven at 50-75°C for more than 20 minutes, then quickly rinsing it with deionized water for 1-3 minutes, and then re-drying it in a vacuum oven at 50-75°C for more than 20 minutes.
[0024] Among them, in step S3, the specific operation of depositing the conductive nanowires is: immersing the porous base fiber after the CNTs conductive layer is deposited in a concentration of 4-6 mg mL -1 in a conductive nanowire solution for more than 20 minutes; the conductive nanowires are AgNWs.
[0025] Wherein, in the step S3, after depositing the conductive nanowires, the following step is also included: drying the porous base fiber after the conductive nanowires in an oven at 50-75° C. for more than 20 minutes.
[0026] Wherein, in step S4, the pre-stretching degree of the microporous structure fiber segment is 100%-150%.
[0027] Wherein, in the step S4, the rubber layer raw material attachment operation is specifically to immerse the microporous structure fiber segment in a uniform rubber layer raw material liquid and keep it in a vacuum dryer for 10-15 minutes.
[0028] Wherein, in the step S4, before the microporous structure fiber segment is pre-stretched, the step further includes cutting the microporous structure fiber obtained in step S3 into segments and connecting leads.
[0029] Wherein, in step S5, the curing operation of the rubber layer raw material is specifically to cure it at 60-65° C. for more than 1 hour.
[0030] The present invention provides a microporous core-sheath fiber-type flexible strain sensor. On the one hand, the deformation ability of the fiber is improved by introducing a stable microporous structure into the porous base fiber. On the other hand, the fiber's ability to match sensitive resistance changes during the deformation process is improved by designing and optimizing the composite conductive network layer on the surface of the porous base fiber, which provides a core foundation for achieving joint improvements in the flexibility, sensitivity, stability and other aspects of the sensor. At the same time, a flexible strain sensor was successfully prepared by matching a suitable rubber layer on the periphery of the microporous structure fiber. While not affecting the performance of the microporous structure fiber, it also further improves the waterproofness, chemical environment stability and other properties of the sensor product. Practical applications show highly sensitive detection results for small changes in gestures. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.
[0032] Figure 1 It is a schematic structural diagram of a specific microporous core-sheath fiber type flexible strain sensor of the present invention.
[0033] Figure 2 This is a schematic diagram of the structure of a specific microporous structure fiber AgNWs / CNTs / EGaIn / TPU of the present invention.
[0034] Figure 3 Schematic diagram of the working principle of the sensor of the present invention.
[0035] Figure 4 The present invention is a process for preparing porous substrate fibers according to a specific embodiment.
[0036] Figure 5 The present invention is a specific embodiment of the preparation process of the composite conductive network layer.
[0037] Figure 6 The relative resistance change curve of the sensor after depositing different concentrations of CNTs.
[0038] Figure 7 The microstructure and macroscopic characteristics of the sensor of the present invention are characterized. Among them, (a) the flexible fiber sensor is tied into a bow; (b) the sensor is collected on a small wheel; (c) the SEM image of the sensor tied with a single knot; (d) the cross-sectional view of the sensor, i. the whole cross-sectional view; ii. the edge of the cross-sectional view; iii. the enlarged edge of the cross-sectional view.
[0039] Figure 8 The stress-strain curves of different fibers.
[0040] Fig. 9 The performance test results of the sensor of the present invention are shown in Figure 1. (a) sensor sensitivity curve; (b) relative resistance change curve at different stretching rates; (c) relative resistance change curve after 5000 50% stretching / releasing cycles of the sensor.
[0041] Fig.10 The stability of the sensor of the present invention in working under unusual environment. Among them, (a) relative resistance change curve at different temperatures; (b) relative resistance change curve of cyclic stretching at 20℃, 40℃ and 60℃; (c) relative resistance change curve of the sensor in acid, alkali and salt solution; (d) relative resistance change curve of the sensor in acid, alkali and salt solution.
[0042] Fig.11 The application of the sensor of the present invention is shown in Figure 1. (a) The sensor is integrated into the five fingers of the glove; (b) The relative resistance change of the sensor on each finger under different gestures. DETAILED DESCRIPTION
[0043] The present invention is further described below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.
[0044] The microporous core-sheath fiber type flexible strain sensor structure provided by the present invention is as follows Figure 1-2 As shown, it includes a microporous structural fiber as a core structure and a rubber layer 2 as a sheath structure, wherein the rubber layer 2 is coated on the periphery of the microporous structural fiber.
[0045] The microporous structure fiber has a porous base fiber 5 , and the surface of the porous base fiber 5 has a composite conductive network layer, and the composite conductive network layer is a carbon nanotube conductive layer 3 (CNTs conductive layer 3 ) having conductive nanowires 1 .
[0046] The working principle of the microporous core-sheath fiber flexible strain sensor is as follows Figure 3 As shown in the figure: when a tensile force is applied to the sensor, the porous base fiber 5, the composite conductive network layer and the overall device of the sensor will deform under the action of the tensile force, resulting in the length of the sensor and the diameter becoming smaller. The porous base fiber 5 has a microporous structure that allows the sensor to have more deformation space, providing conditions for the sensor to achieve large-scale detection and is conducive to enhancing the structural matching degree with the stretching of the rubber layer 2. During the stretching deformation process of the sensor, the composite conductive network layer (AgNWs / CNTs) changes, and the connection points between the criss-crossed AgNWs decrease due to stretching, and the AgNWs conductive path decreases accordingly. At this time, the dense CNTs act as a conductive bridge between the AgNWs, and this process leads to an increase in the resistance of the device. When the tensile force disappears, the fiber base, the composite conductive network and the overall device will return to their original state, and the resistance will also return to its original value. The change in resistance can be converted into an electrical signal and transmitted to the subsequent processing circuit, thereby monitoring the magnitude of the force.
[0047] The porous base fiber 5 of the microporous structure fiber has micropores of about 0.1 to 5 μm and microholes of about 10 to 150 μm; the micropores and microholes have a passivated oxide layer inner surface. The introduction of the microporous structure improves the tensile deformation ability, recovery ability and toughness of the porous base fiber 5, and is not easy to collapse and fail. At the same time, it is conducive to forming a passivated oxide layer inner surface, improving the stability of the structure itself, and together with the rubber layer 2, maintains good environmental stability and thermal stability and other properties.
[0048] The matrix material of the porous base fiber 5 of the microporous structure fiber is TPU, and the inner surface of the passivated oxide layer is a metal oxide layer, preferably a Ga2O3 oxide layer; in the raw material of the porous base fiber 5, the liquid metal that can form the metal oxide layer is 1% to 10% of TPU, preferably 2.5% to 6.25%.
[0049] The thickness of the composite conductive network layer can be 50-1500nm, preferably 500±200nm. The thickness of the composite conductive network layer is substantially the thickness of the CNTs conductive layer 3, and the conductive nanowires 1 are rod-shaped nanowire structures, so a dense deposition layer will not be formed. Optimizing the thickness of the composite conductive network layer is beneficial to balancing the tensile deformation and conductivity of the composite conductive network layer (especially the CNTs conductive layer 3), and is also beneficial to quickly adjusting the staggered connection of the conductive nanowires 1 during the tensile deformation process.
[0050] The conductive nanowires 1 may be silver nanowires (AgNWs), copper nanowires, gold-silver nanowires, or other nanowire products with good conductivity in the prior art.
[0051] The rubber layer 2 is made of a two-component liquid silicone rubber material with good flexibility, preferably Ecoflex rubber, which can be purchased commercially, such as Ecoflex00-10 to Ecoflex00-50 series, etc. The two-component liquid silicone rubber can play a good passivation and protection role on the microporous structure fiber on the one hand, and has good adhesion with the composite conductive network layer on the other hand, and can perform good deformation matching during the tensile deformation of the microporous structure fiber, ensuring good overlap of the staggered connection of the conductive nanowires 1 during the change process.
[0052] The method for preparing the microporous core-sheath fiber type flexible strain sensor comprises the following steps:
[0053] S1: preparing a spinning solution containing sodium chloride, a matrix material (TPU) and a liquid metal (EGaIn);
[0054] S2: Preparation of porous substrate fibers with stable microporous structure by wet spinning;
[0055] S3: sequentially depositing a CNTs conductive layer 3 and a conductive nanowire 1 on the surface of the porous base fiber to obtain a microporous structure fiber that can be used to further prepare a microporous core-sheath fiber type flexible strain sensor;
[0056] S4: attaching the rubber layer 2 raw material in an uncured state to the surface of the microporous structure fiber segment in a pre-stretched state;
[0057] S5: Curing the rubber layer 2 raw material to obtain a sensor product.
[0058] In the step S1, the spinning solution components include sodium chloride, a matrix material solution, and a liquid metal diluent mixed in a weight ratio of 1:50:5-2:50:5, the matrix material solution is TPU and DMF mixed in a weight ratio of 1:3-1:5, and the liquid metal diluent is EGaIn and ethanol mixed in a weight ratio of 1:8-1:12.
[0059] In the step S2, the specific process of wet spinning is to extrude the spinning solution into a coagulation bath through a syringe, and after stabilizing in the coagulation bath, dry to obtain a porous base fiber; the coagulation bath is a mixture of ethylene glycol and deionized water with a specific gravity of 1:1-1:1.2. DMF and ethylene glycol can cooperate to form countercurrent diffusion, which helps to form microporous microcavities. The solvent system of ethanol and DMF prevents the sodium chloride in the spinning solution from dissolving before entering the coagulation bath. At the same time, ethanol reconciles the compatibility of DMF and deionized water as solvents. The solvent in the spinning solution forms a good match with the coagulation bath, which is conducive to the formation of a microporous structure in the fiber of the present invention. In the step S2, the residence time of the spinning solution in the coagulation bath after extrusion molding is more than 20 minutes, so that the pore structure is fully formed and stable, preferably 20-120 minutes, and more preferably 30-40 minutes.
[0060] In the step S2, after the spinning solution is extruded and stabilized in the coagulation bath, the drying condition is 50-70° C. for more than 2 hours.
[0061] In the step S3, the specific operation of depositing the CNTs conductive layer 3 is: subjecting the porous base fiber to ultrasonic treatment at a temperature of 0-5°C and a power of 350-400W for 15-25 minutes.
[0062] In the step S3, before depositing the CNTs conductive layer 3 and the conductive nanowires 1 respectively, the following step is also included: drying the porous base fiber after depositing the CNTs conductive layer 3 in an oven at 50-75°C for more than 20 minutes, then quickly rinsing it with deionized water for 1-3 minutes, and then re-drying it in a vacuum oven at 50-75°C for more than 20 minutes.
[0063] In the step S3, the specific operation of depositing the conductive nanowires 1 is as follows: immersing the porous base fiber after depositing the CNTs conductive layer 3 in a solution having a concentration of 4-6 mg mL -1 in a conductive nanowire solution for more than 20 minutes; the conductive nanowires are AgNWs.
[0064] In the step S3, after depositing the conductive nanowires 1, the method further comprises the following step: drying the porous substrate fibers formed by the conductive nanowires 1 in an oven at 50-75° C. for more than 20 minutes.
[0065] In step S4, the pre-stretching degree of the microporous structure fiber segment is 100%-150%. Pre-stretching is beneficial to the adhesion of the rubber layer 2 and the matching of the deformation capacity of the rubber layer 2 during the use of the stretching deformation.
[0066] In the step S4, the rubber layer 2 raw material attachment operation is specifically to immerse the microporous structure fiber segment in a uniform rubber layer 2 raw material liquid and keep it in a vacuum dryer for 10-15 minutes.
[0067] In the step S4, before the microporous structure fiber segment is pre-stretched, the step also includes cutting the microporous structure fiber obtained in step S3 into segments and connecting leads.
[0068] In the step S5, the curing operation of the rubber layer 2 material is specifically to cure it at 60-65° C. for more than 1 hour.
[0069] The following is further described by a specific embodiment of the present invention. The preparation process of the core-sheath fiber type flexible strain sensor with a multi-microporous structure in this embodiment is as follows:
[0070] (1) Thermoplastic polyurethane (TPU) particles and dimethylformamide (DMF) solution are weighed in a weight ratio of 1:3-1:5 and placed in a beaker, and magnetically stirred at 50-70° C. for 3-6 hours to obtain a uniform thermoplastic polyurethane spinning solution.
[0071] (2) The eutectic gallium-indium alloy (EGaIn) and the ethanol solution were weighed in a weight ratio of 1:8-1:12 and placed in a beaker, and then ultrasonically treated at 0-5° C. and 280-350 W for 20-40 min to prepare an EGaIn dilution solution.
[0072] (3) First, weigh the sodium chloride particles, the TPU solution in (1) and the EGaIn dilution in (2) in a weight ratio of 1:50:5-2:50:5 and put them into a beaker, and stir them manually for 1-4 minutes to obtain a uniform spinning solution. Then use a 5mL medical syringe as a spinning syringe to steadily extrude the spinning solution into a coagulation bath through the syringe needle at a rate of 0.09mm / s-0.12mm / s, wherein the coagulation bath is a mixture of ethylene glycol and deionized water with a specific gravity of 1:1-1:1.2. Then leave the extruded fiber in the coagulation bath for 30-40 minutes to obtain a stable porous structure, and then collect it on a small wheel. Finally, dry the formed fiber in an oven at 50-70°C for 5-8 hours to completely evaporate the solvent to obtain a porous base fiber with EGaIn / TPU ( Figure 4 ).
[0073] (4) Carbon nanotubes (CNTs), sodium dodecyl sulfate (SDS) and deionized water were placed in a beaker at a weight ratio of 70:7:10000, 80:8:10000, 90:9:10000 and 10:1:1000, respectively, and ultrasonically treated at a temperature of 0-5°C and a power of 300-400 W for 20-50 min to obtain a uniform CNTs solution.
[0074] (5) The EGaIn / TPU porous substrate fiber prepared in (3) is immersed in a CNTs solution, and ultrasonically treated at a temperature of 0-5°C and a power of 350-400W for 15-25 minutes to obtain a microporous structure fiber CNTs / EGaIn / TPU with CNTs deposited. The fiber is then taken out and dried in an oven at 50-75°C for 40-60 minutes, and then quickly rinsed with deionized water for 1-3 minutes to remove loosely attached CNTs particles, and re-dried in a vacuum oven at 50-75°C for 20-40 minutes.
[0075] (6) The CNTs / EGaIn / TPU fibers obtained in (5) were immersed in a 4-6 mg / mL -1 The AgNWs solution was placed in a vacuum oven at 50-70°C for 40-70 minutes to obtain a microporous structure fiber AgNWs / CNTs / EGaIn / TPU ( Figure 2 , 5 ).
[0076] (7) The flexible sensor fiber in (6) was cut into small segments of 4-6 cm, and silver-plated nylon wires were connected on both sides of the fiber segments using conductive silver paste as sensor leads.
[0077] (8) The two-component raw materials of Ecoflex rubber are mixed in a container at a ratio of 1:1, and then the AgNWs / CNTs / EGaIn / TPU fiber segment obtained in (7) is pre-stretched by 100%-150% (i.e., stretched to 2 times-2.5 times of the original length) and immersed in the Ecoflex rubber mixture, and kept in a vacuum dryer for 10-15 minutes to remove bubbles. The fiber is then taken out of the Ecoflex rubber mixture and cured at 60-65°C for 1-2 hours, and finally a core-sheath fiber-type flexible strain sensor with a porous structure and a composite conductive network is obtained ( Figure 1 ).
[0078] The sensor prepared by the present invention is tested and characterized below.
[0079] Figure 6The relative resistance change curve of the sensor obtained after depositing different concentrations of CNTs is shown. By using different concentrations of CNTs solution: CNTs: SDS: H2O (wt%) = 70: 7: 10000 (0.7wt%), 80: 8: 10000 (0.8wt%), 90: 9: 10000 (0.9wt%), 10: 1: 1000 (1.0wt%), a composite conductive network layer with different CNTs deposition concentrations was prepared. It can be seen that with the increase of CNTs deposition concentration, the sensor sensitivity first increases and then decreases, and reaches the optimum at a CNTs deposition concentration of 0.9wt%.
[0080] Figure 7 The microstructure and macroscopic properties of the sensor of the present invention are shown. The sensor of the present invention has ultra-high flexibility and can be tied into a bow ( Figure 7 a), and the sensor can be collected in large quantities on a small wheel, indicating that it can be prepared in batches ( Figure 7 b). The sensor with a single knot was observed under an electron microscope (SEM), and it can be seen that the structure is intact and not easily damaged ( Figure 7 c). By observing the SEM cross-sectional image of the sensor ( Figure 7 d), the entire cross section can be seen, and there are multiple micropores of different sizes; zooming in on the edge of the cross section, it can be seen that CNTs and AgNWs exist, and the thickness of the composite conductive network layer is about 463nm.
[0081] The microporous structure in the porous base fiber of the present invention is obtained by dissolving NaCl particles in a coagulation bath to obtain smaller micropores, countercurrent diffusion of DMF and ethylene glycol causes the fiber to coagulate and obtain larger microholes, and the addition of EGaIn allows each hole inside the fiber to form a self-passivating Ga2O3 oxide layer, so that the surface of the micropore has structural self-stability and plasticity, thereby increasing the elongation rate (breaking elongation rate of 570%) and toughness of the fiber as a whole. The composite conductive network layer formed by the CNTs conductive layer and the AgNWs conductive layer is more stable than the previous single-layer conductive structure. Ecoflex rubber is applied in the pre-stretched state of the fiber to play a passivation role and will not affect the tensile properties of the fiber, which makes the sensor have a higher sensitivity (GF reaches 7336.1), further improving the waterproofness, chemical environment stability, thermal stability, etc.
[0082] Figure 8The stress-strain curves of different fibers are compared and the improvement effect of the above structure on the tensile performance of the sensor is verified. It can be seen that the ultimate elongation of pure TPU fiber is only 320% and the breaking stress is 8MPa, while the ultimate elongation of the EGaIn / TPU porous substrate fiber in the present invention can reach 570%, and the breaking stress is more than 12MPa, and the deposition of the composite conductive network has almost no effect on the tensile performance (AgNWs / CNTs / EGaIn / TPU). It can be seen that the sensor fiber obtained by wet spinning of a mixed solution of NaCl, TPU solution and EGaIn diluent proposed by the present invention has improved elongation and toughness.
[0083] Fig. 9 The performance test results of the sensor of the present invention are shown, and the above structure is verified to improve the performance of the sensor in terms of sensitivity and stability. The sensitivity of the sensor prepared using CNTs: SDS: H2O (wt.%) = 90:9:10000 is GF 52.7 under low stretching and GF 7336.1 under high stretching. Fig. 9 a); The sensor can obtain the corresponding relative resistance change when stretched by 10%, 50%, 100%, 150%, 450%, 470%, and 500% ( Fig. 9 b); After 5000 times of 50% stretching / releasing, the relative change in resistance of the sensor is very consistent, proving the good stability of the sensor ( Fig. 9 c).
[0084] Fig.10 This shows the stability of the sensor in an abnormal environment, further verifying the effect of the above structure on the chemical environment stability of the sensor. The relative resistance value of the sensor changes very little in a temperature environment of -20℃-80℃ ( Fig.10 a), and a regular relative resistance change curve can be obtained by performing 30%, 60%, 90%, and 120% stretching cycles at 20°C, 40°C, and 60°C, respectively ( Fig.10 b); The resistance value of the sensor changes very little in acid, alkali and salt solutions ( Fig.10 c), and a regular relative resistance change curve can be obtained by performing 30%, 60%, 90%, and 120% stretching cycles in acid, alkali, and salt solutions, respectively ( Fig.10 d). The results show that the sensor of the present invention has good waterproofness, chemical environment stability, thermal stability and other characteristics.
[0085] Fig.11The application performance of the sensor of the present invention is shown. Five sensors are integrated into the five fingers of the glove. The silver-plated nylon wire connects the two ends of the fiber through conductive silver paste. The connection is fixed to the glove with tape to achieve stable testing. After the sensor is integrated into the fabric glove, it can bend with the fingers ( Fig.11 a), by bending the finger, the length of the sensor increases, and the resistance value increases; when the finger is straightened, the sensor returns to its original state, and the resistance value is restored. Therefore, different gestures can be made by bending the finger differently, and different relative resistance signal changes can be obtained ( Fig.11 b). The test results show that the sensor of the present invention can be well applied in wearable flexible products.
[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A microporous core-sheath fiber type flexible strain sensor, comprising a microporous structural fiber as a core structure and a rubber layer as a sheath structure, wherein the rubber layer is coated on the periphery of the microporous structural fiber, the microporous structural fiber has a porous base fiber, and the surface of the porous base fiber has a composite conductive network layer, wherein the composite conductive network layer is a carbon nanotube conductive layer having conductive nanowires, and the carbon nanotube conductive layer and the conductive nanowires are sequentially deposited on the surface of the porous base fiber.
2. The microporous core-sheath fiber type flexible strain sensor according to claim 1, characterized in that: The porous base fiber of the microporous structural fiber has micropores of 0.1 to 5 μm and microcavities of 10 to 150 μm; The micropores and microcavities have passivated oxide layer inner surfaces.
3. The microporous core-sheath fiber type flexible strain sensor according to claim 1, characterized in that: The base material of the porous base fiber of the microporous structure fiber is TPU, and the inner surface of the passivated oxide layer is a metal oxide layer; in the raw material of the porous base fiber, the liquid metal that can form the metal oxide layer is 1% to 10% of the TPU.
4. The microporous core-sheath fiber type flexible strain sensor according to claim 1, characterized in that: The thickness of the composite conductive network layer is 50-1500nm.
5. The microporous core-sheath fiber type flexible strain sensor according to claim 1, characterized in that: The conductive nanowires are one or more of silver nanowires, copper nanowires, and gold-silver nanowires; The rubber layer is made of two-component liquid silicone rubber material.
6. A method for preparing the microporous core-sheath fiber type flexible strain sensor according to any one of claims 1 to 5, comprising the following steps: Step S1: preparing a spinning solution containing sodium chloride, a matrix material and liquid metal; Step S2: preparing porous base fibers with a stable microporous structure by wet spinning; Step S3: sequentially depositing a CNTs conductive layer and a conductive nanowire on the surface of the porous base fiber to obtain a microporous structure fiber that can be used to further prepare a microporous core-sheath fiber type flexible strain sensor; Step S4: attaching the rubber layer raw material in an uncured state to the surface of the microporous structure fiber segment in a pre-stretched state; Step S5: solidifying the rubber layer raw material to obtain a sensor product.
7. The method for preparing the microporous core-sheath fiber type flexible strain sensor according to claim 6, characterized in that: In the step S1, the spinning solution components include sodium chloride, a matrix material solution, and a liquid metal diluent mixed in a weight ratio of 1:50:5-2:50:5, the matrix material solution is TPU and DMF mixed in a weight ratio of 1:3-1:5, and the liquid metal diluent is EGaIn and ethanol mixed in a weight ratio of 1:8-1:
12.
8. The method for preparing the microporous core-sheath fiber type flexible strain sensor according to claim 6, characterized in that: In the step S2, the specific process of wet spinning is to extrude the spinning solution into a coagulation bath through a syringe, and after stabilizing in the coagulation bath, dry it to obtain a porous base fiber; the coagulation bath is a mixture of ethylene glycol and deionized water with a specific gravity of 1:1-1:1.2; in the step S2, the spinning solution stays in the coagulation bath for more than 20 minutes after being extruded and formed; In the step S2, after the spinning solution is extruded and stabilized in the coagulation bath, the drying condition is 50-70° C. for more than 2 hours.
9. The method for preparing a microporous core-sheath fiber type flexible strain sensor according to claim 6, characterized in that: In the step S3, the specific operation of depositing the CNTs conductive layer is: subjecting the porous base fiber to ultrasonic treatment at a temperature of 0-5° C. and a power of 350-400 W for 15-25 min; In the step S3, before the CNTs conductive layer and the conductive nanowires are deposited respectively, the following steps are further included: drying the porous base fiber after the CNTs conductive layer is deposited in an oven at 50-75° C. for more than 20 minutes, then quickly rinsing with deionized water for 1-3 minutes, and then re-drying in a vacuum oven at 50-75° C. for more than 20 minutes; In step S3, the specific operation of depositing the conductive nanowires is: immersing the porous substrate fiber after the CNTs conductive layer is deposited in a solution having a concentration of 4-6 mg mL -1 The conductive nanowires are AgNWs. In the step S3, after depositing the conductive nanowires, the following step is further included: drying the porous base fiber after the conductive nanowires in an oven at 50-75° C. for more than 20 minutes.
10. The method for preparing a microporous core-sheath fiber type flexible strain sensor according to claim 6, characterized in that: In step S4, the pre-stretching degree of the microporous structure fiber segment is 100%-150%; In the step S4, the rubber layer raw material attachment operation is specifically to immerse the microporous structure fiber segment in a uniform rubber layer raw material liquid and keep it in a vacuum dryer for 10-15 minutes; In the step S4, before the microporous structure fiber segment is pre-stretched, the microporous structure fiber obtained in step S3 is cut into segments, and lead wires are connected; In the step S5, the rubber layer raw material is cured at 60-65° C. for more than 1 hour.
Citation Information
Patent Citations
Flexible wearable strain sensor and preparation method thereof
CN106052544A
Preparation methods for composite nanofiber membrane and flexible strain sensor
CN112900080A